PERAN DINAS PENDIDIKAN KOTA PEKANBARU DALAM MEWUJUDKAN AKSES PENDIDIKAN YANG MERATA DAN BERMUTU TAHUN 2018 - Reza Pradana Nugraha; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Education is something that is very essential in the humanitarian process in a cultured society. So in practice, every child has the right to get an education which has become his right to obtain an education that is accessible and of good quality. There are various kinds of problems to make it happen, such as education infrastructure such as school spaces that are still lacking, and the low quality of education is caused by the number of teachers who are not evenly distributed and the level of teacher welfare cannot be said to be good, especially teachers who are not civil servants. There are two problem formulations in this research, namely "How is the role of the Pekanbaru city education office in realizing equal and quality access to education and the inhibiting factors in its implementation".The research approach used is a qualitative approach. while the type of research used is descriptive. The data was collected by the author using interview and documentation techniques. The data used are primary data obtained from research informants and further supported by secondary data obtained from various government agencies related to this research.The results showed that the Education Office made various efforts in order to achieve equal and quality access to education in Pekanbaru City. This is supported by increasing the role of the government, in this case the education office. Efforts are being made to use the theory of the role of government, namely (1) Role as community service, (2) Role as facilitator, (3) Role as companion, (4) Role as partner, (5) Role as funder. In carrying out its duties and functions in realizing equitable and quality access to education, the Pekanbaru City Education Office experiences several obstacles such as limited budget and human resources. Keywords: Role, Even and Quality Education, Education Office